2021
DOI: 10.21111/dnj.v5i1.5876
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan pola makan, aktivitas fisik, kualitas tidur dengan status gizi santriwati Pondok Modern Darussalam Gontor Putri 1

Abstract: Masa remaja merupakan masa tumbuh kembang anak hingga dewasa, pada masa ini akan mengalami beberapa perubahan yang terdiri dari fisik dan psikis. Masa remaja sangat membutuhkan lebih banyak zat gizi karena membantu meningkatkan pertumbuhan fisik dan perkembangan yang lebih baik. Penyebab status gizi pada remaja dapat dipengaruhi oleh faktor ketidakseimbangan antara pola makan, aktivitas fisik, dan kualitas tidur. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan pola makan, aktivitas fisik dan kualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
4
5
0
4
Order By: Relevance
“…The result of this research was also parallel with the research (Nabawiyah et al, 2021) which stated that there was no correlation between sleep quality and nutritional status in Gontor Putri I. This was caused by the data collection in the boarding school.…”
Section: B) Sleep Qualitysupporting
confidence: 77%
“…The result of this research was also parallel with the research (Nabawiyah et al, 2021) which stated that there was no correlation between sleep quality and nutritional status in Gontor Putri I. This was caused by the data collection in the boarding school.…”
Section: B) Sleep Qualitysupporting
confidence: 77%
“…Likewise, Widyantari et al also found a relationship between physical activity, diet and family income with the incidence of obesity in elementary school children (9) . Furthermore, Nabawiyah et al found a relationship between eating pa erns, physical activity, and sleep quality with nutritional status in female students (10) .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another study showed that during the COVID-19 pandemic, 18.8% of students had poor consumption patterns by not paying attention to nutritional guidelines and nutritional content in the food consumed 24 . Disruption of sleep and consumption patterns can affect the nutritional status of students 25,26 . Accordingly, researchers aimed to study the relationship between energy intake, macronutrients, and sleep duration with the nutritional status of new students of the Faculty of Public Health (FKM), Universitas Airlangga (UNAIR).…”
Section: Association Between Energy and Macronutrient Intake And Slee...mentioning
confidence: 99%